An Overview of Clean and Healthy Living Behavior Practices in the Islamic Boarding-Based Education (Pondok Pesantren) Environment - Fajrul Falah Farhany; Ichlasul Amalia; Meyka Budi Rachmawati; Winda Ernia; Hanggoro Tri Rinonce; Happy Indah Kusumawati; Rahadyana Muslichah (Journal of Community Empowerment for Health, 2023)
Introduction: Perilaku hidup bersih dan sehat (PHBS) or also called clean and healthy living behavior (CHLB) in English practices in a congregate setting such as Islamic boarding schools (IBS) or pondok pesantren plays a vital role in maintaining the health of each individual living in the area. This study aimed to provide an overview of students (santri)’ CHLB practices at the Assalafiyyah Mlangi II Terpadu IBS. Methods: This quantitative non-experimental study was conducted using a survey method in July-September 2022. A non-probability sampling with a total sampling of 841 students was used. The data were collected using self-administered questionnaires developed on Google Forms and imported to Microsoft Excel for further data analysis. Additional observations of the environment and student activities were also used. Several indicators were assessed, including personal health maintenance, CHLB implementation, and environmental cleanliness. Results: The results showed that the students consume fruit less than 2 times per day (more than 80%), vegetables less than 3 times per day (male student 42.33% and female student 50.7%), drinking 6-9 glasses of water (18%), none of the female students (0.00%) have routine exercise schedule with the duration 90-120 minutes per week, and only female students (56.90%) have regular sleep patterns of 6-8 hours per day. The CHLB practices implementation and environmental cleanliness used the indicators of good handwashing practices, regular bathroom and dormitories cleaning, and the overall cleanliness of the Islamic boarding school achieved good performance, which scored more than 40%. Meanwhile, 44.04-67.85% of the students reported average scores for the available cleaning and healthcare facilities. Conclusion: In general, according to students’ perceptions, implementing CHLB at the Assalafiyyah Mlangi II Terpadu IBS is good enough, but the medical equipment is insufficient. Additionally, the condition of the school health unit or UKS is inadequate, so it is necessary to improve infrastructure and medicines. Furthermore, healthy santri cadres are needed as role models for other students in implementing CHLB and improving health status through promotive and preventive efforts.